Stereotactic/hypofractionated body radiation therapy as an effective treatment for lymph node metastases from colorectal cancer: an institutional retrospective analysis - Franzese, Ciro (Br J Radiol, 2017)
OBJECTIVE: The colorectal cancer (CRC) might present loco-regional recurrence, including lymph-node metastasis. Stereotactic body radiotherapy (SBRT) is a non-invasive and well-tolerated ablative treatment. Aim of the present study is to evaluate efficacy and toxicity of SBRT with volumetric modulated arc therapy (VMAT) in this setting. METHODS: 35 patients presenting a total of 47 nodal recurrences from CRC, treated with VMAT-SBRT from 2008 to 2015, were selected. About three fourth of the treatments delivered 45 Gy in 6 daily fractions. End-points were the detection of toxicities, overall survival (OS), local control (LC), disease progression free incidence (DPFI) and disease free survival (DFS). Tumour response was assessed according to the RECIST criteria. RESULTS: Only Grade 1 and 2 toxicities were recorded. Median follow-up was 15 months (range 2–68). Local relapse was reported in 6 patients, regional relapse in 10 patients. Complete remission was reported in 20 cases (53%), partial remission in 14 (37%). Rates of LC at 1, 2 and 3 years were 85.3, 75.0 and 75.0%, respectively. At 1 year the actuarial OS was 100%, at 2 and 3 years was 81.4%. Median DFS was estimated in 16 months, with an incidence of 69.4, 33.3 and 19.4% at 1, 2 and 3 years, respectively. CONCLUSION: The use of the VMAT-SBRT in lymph-node recurrence of CRC could prevent severe complications and achieve satisfying rates of disease control. ADVANCES IN KNOWLEDGE: The use of VMAT-SBRT is a viable approach for lymph-node recurrence of CRC.